Dark places: environmental education research in a world of hyperobjects. Issue 9 (2nd October 2020) - Saari, Antti; Mullen, John
Abstract: Escalating ecological events like global warming haunt our lived experience of place and demand thinking the concept anew in environmental education research. Using Timothy Morton's notions of hyperobjects and dark ecology as a springboard, we articulate the uncanny—the withdrawn, unknowable, excessive and anxiety-provoking—aspects of place that events like global warming disclose for place-based pedagogies. Given the advent of hyperobjects as a theoretical model coupled with the ontological and ethical attunement of dark ecology, we suggest conceptualizing place through the strategies of juxtaposition and working-through in order to begin thinking through the implications of how to live in dark places that are haunted by the reality of hyperobjects.